The Tatler '06 (1906) - Henry C. Chiles (Editor-in-Chief); Lee Graham (Business Manager); Ara R. Ash (Associate Editor); Alfred D. Pittman (Literary Editor); John S. Custer (Organization Editor); L. Dean Sands (Art Editor); A.D. McGlashan (Circulation Manager); John E. Davis (Advertising Manager) (William Jewell College (Liberty, MO), 1906)
Tatlers were William Jewell College's official yearbook publication, released every year by the student body.